2006
DOI: 10.1111/j.1467-9280.2006.01808.x
|View full text |Cite
|
Sign up to set email alerts
|

Hungry for Money

Abstract: This report attempts to provide an evolutionary explanation for humans' motivation to strive for money in present-day societies. We propose that people's desire for money is a modern derivate of their desire for food. In three studies, we show the reciprocal association between the incentive value of food and of money. In Study 1, hungry participants were less likely than satiated participants to donate to charity. In Study 2, participants in a room with an olfactory food cue, known to increase the desire to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(81 citation statements)
references
References 24 publications
2
77
2
Order By: Relevance
“…The desire for money and caloric resources are highly intertwined, such that the desire for money increases the desire for caloric resources, and vice-versa (29). Therefore, low social status, and poverty in particular, may lead to an increased desire for food, and an increased perception that the food supply is inadequate or may be in the near future, even when high calorie, energy dense foods are available.…”
Section: Evidence That Low Food Security Influences Body Fat Stores Smentioning
confidence: 99%
“…The desire for money and caloric resources are highly intertwined, such that the desire for money increases the desire for caloric resources, and vice-versa (29). Therefore, low social status, and poverty in particular, may lead to an increased desire for food, and an increased perception that the food supply is inadequate or may be in the near future, even when high calorie, energy dense foods are available.…”
Section: Evidence That Low Food Security Influences Body Fat Stores Smentioning
confidence: 99%
“…The authors noted that resource-deprived mindset may lead individuals to perceive the world as competitive, becoming more prone to zero-sum beliefs. Although scarcity arises in various domains (e.g., financial and calorie), there is a common overlap among the diverse experiences of scarcity (Muraven and Baumeister, 2000; Briers et al, 2006). Sleep replenishes depleted resource (Saper et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Ijzerman and Semin (2009) found that thermal manipulations (e.g., holding a warm or cool cup) impacted both social proximity and relational language use. A number of studies have similarly found that both hunger and glucose depletion can modulate prosocial decision-making, resulting in less altruistic behavior (e.g., Briers, Pandelaere, Dewitte, & Warlop 2006; DeWall, Baumeister, Gailliot, & Maner, 2008; although cf. Aarøe & Petersen, 2013).…”
Section: Interoception and Interoceptive Dysfunction: An Introductionmentioning
confidence: 99%